PENGARUH PASCA PANDEMI COVID-19 TERHADAP MOTIVASI PERJALANAN WISATA KE ANYER BANTEN - Eka Indah Yuslistyari; Chotibul Umam; Gina Ramayanti (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2023)
The purpose of the study was to analyze the effect of post-covid-19 on the motivation of tourist trips to Anyer Beach Banten. The research variables are post-covid-19 (X) and tourist travel motivation (Y). Sample determination using the slovin method amounted to 101 respondents. Data collection using a questionnaire with a Likert scale (5 scale). Data processing using SPSS Version 21 with data quality testing, namely data validity and reliability tests, correlation coefficients, classical assumption tests, simple regression analysis, hypotheses (T test and F test) and matrix correlation between dimensions. The results showed that post covid-19 had a positive and significant effect on travel motivation, with an R Square value of 0.291, meaning that there was a post covid-19 influence on travel motivation of 29.1% while the remaining 70.9% was influenced by other factors. The results of the matrix correlation between the dimensions of maintaining distance and the personal dimension have the largest value, namely 0.458. This shows that the better the management of services and facilities provided to tourists on Anyer Beach with health protocols and limiting the level of post-Covid-19 crowds will increase the motivation for tourist trips to Anyer Beach, on the contrary, the worse the management of services and facilities provided to tourists on Anyer Beach, the lower the motivation for tourist trips to Anyer beach.